Differentiating Pathogenic Bacteria through Biochemical Markers: A Study for Clinical Applications - Anusha Ravi; Swati Chandrakant Hosvakka; Sumana Kumar; Radhika Vaidya (Oral Sphere Journal of Dental and Health Sciences, 2025)
Introduction: Beer has become the world's largest consumed alcohol. Beer brewed on a small scale in terms of quantity by independent breweries that brew traditionally has been termed as craft beer. Small-scale breweries involve testing newer preparation techniques, which also involve the use of raw materials not commonly accepted. However, these practices can increase the incidence of contaminants, awareness of which helps consumers make informed choices. Contamination can occur at any stage of the production process, and microbial contaminants may either improve or deteriorate the quality of beer by producing biochemicals and organic acids, affecting the beer's shelf life. Aim: To analyse various local craft beer samples for contaminants, with a focus on microbial contamination. Methods: Samples of the local craft beers were taken and screened. The samples were diluted serially and spread plated on simple agar media for isolation. Gram staining and biochemical characterisation of bacterial colonies Results: There are several kinds of microorganisms identified to exist in local craft beers. Their existence is detected through the characteristic and biochemical profiling in the samples. Conclusion: The study indicates the presence of microbial contamination in local craft beer, thereby showing the possible effects of such contamination on quality and shelf life. Consumers and producers could use this information to guide decisions to produce and consume craft beers.